Ruiz Berrio, J. (dir.); Martínez Navarro, A.; Colmenar, C. y Carreño, M. (2002). La editorial Calleja, un agente de modernización educativa en la restauración. - Ramos Zamora, Sara (Revista Complutense de Educación, 2002)
Sin resumen